PENGALAMAN HIDUP REMAJA YANG HAMIL DI LUAR NIKAH (Studi Fenomenologi Di Desa Baru Kecamatan Ibu Halmahera Barat) - Devisolita Malik; Athanasia Budi Astuti; Natalia R Yulianti (Universitas Kristen Satya Wacana, 2015)
The life of an unmarried pregnant teen is a depressed one due to the racism and discrimination received by her. Depression during pregnancy influences the increasing of morbidity toward the mother and the baby. This is because the pregnant teen tends to harm herself and the fetus during the depression. Teenage pregnancies contribute 50% to maternal and child mortality. The purpose of this research is to scrutinize the life experience of an unmarried teen girl in Baru Village, Ibu District, West Halmahera. Method being used is: qualitative research and phenomenology approach. Two pregnant teen girls are the participants, chosen using purposive sampling. Data is gathered by in-depth interview, analyzed using van Manen method (Hermeneutic Analysis). Validity test is using four criteria: credibility, transferability, dependability, and confirmability. Result of the research shows that the life experience of an unmarried pregnant teen girl is a stressful and traumatic experience. Early stage of pregnancy is passed by responding the pregnancy in silent and thinking positively, along with great fear. Due to the demands of the ‘situation’, she pushes herself to adapt to the changes inside her and the social system around her. Related to the respond of her surroundings to her pregnancy, she tends to change the subject, avoid the subject or lying. Pressure felt by her comes from herself (guilty, shame, sorry, and anger) and her surroundings (excommunicated, slandered). Decisions made by her due to the circumstances: abortion (fail), commits suicide, gives the baby to adopt, or gets married. However, all the difficulties bring harm to the girl that influences her life: her status as a mother, more mature point of view, and trauma to pregnancy. Keywords: Life Experience, Teen Girl, Unmarried Pregnancy.